Light Inhibits Lens-Induced Myopia through an Intensity-Dependent Dopaminergic Mechanism - Cindy Karouta, PhD; Kate Thomson, PhD; Ian Morgan, PhD; Regan Ashby, PhD (Ophthalmology Science)
Purpose: Bright light exposure has been postulated to underlie the ability of time spent outdoors to prevent the development of myopia in humans. In support of this, bright light inhibits the development of form-deprivation myopia (FDM) in all species studied. While lens-induced myopia (LIM) is also inhibited by bright light in most species, it remains unclear whether this is brought about in an intensity-dependent manner and whether dopamine (DA) plays the same critical role in this paradigm as is seen in FDM. Design: An experimental study. Subjects: White Leghorn chickens (Gallus gallus). Methods: To examine the effect of light on LIM, chicks fit with lenses of −10 diopters were exposed to 500, 20 000, or 40 000 lux for 14 days (n = 6 per group). To assess the role of DA, its levels were measured 30 minutes after light exposure in previously dark-adapted animals over 6 light intensities (between dark and 40 000 lux). In a separate experiment, a D1-like (SCH-23390) or D2-like (spiperone) receptor antagonist was administered (once daily) to chicks wearing negative lenses under 40 000 lux (n = 5 to 6 per group) for a period of 5 days. Main Outcome Measures: Refraction (infrared photoretinoscopy), axial length (A-scan ultrasonography), and DA levels (liquid chromatography-tandem mass spectrometry). Results: Bright light inhibited LIM in an intensity-dependent manner (P < 0.05) but did not prevent full compensation. The protection afforded by bright light was significantly reduced by administration of spiperone (D2-like, P < 0.05), but not SCH-23390 (D1-like, P = 0.77). Retinal DA levels showed an intensity-dependent increase (P < 0.05). Conclusions: As previously observed for FDM, bright light can inhibit the development of LIM in an intensity-dependent manner. This protection occurs, at least in part, via a DA-dependent mechanism. However, bright light's inability to prevent compensation to negative lenses is indicative of mechanistic differences between the 2 experimental models of myopia. These differences are most likely linked to the presence of a defocus-driven end point for growth in LIM that is not present in FDM. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.